Praktik Budi Daya Padi Berwawasan Ekologis: Kasus di Indramayu - Sarwititi Sarwoprasodjo; Suryo Wiyono; Said Abdullah; Ayu Rahayu; Bayu Aji Krisandi; Anjar Kartika; Anisa Nurkasanah; Dyah Harianti Purnomo (Institut Pertanian Bogor, 2023)
Climate change affects the agricultural sector, which has an impact on droughts or floods. Ecological agriculture is expected to be an adaptation method for reducing losses due to climate change. This study aims to describe the characteristics of farmers, ecological rice cultivation practices, and the relationship between the two parameters. The research in Kendayakan Village, Terisi District, Indramayu Regency, involved 60 farmers surveyed using accidental sampling techniques in February 2022. The data collected include farmer characteristics (age, education, land area, land ownership status), length of farming, sources of farming knowledge, participation in groups, and rice cultivation practices. Data on the application level of ecological agricultural practices were analyzed descriptively and tested usin the Spearman Rank correlation between farmer characteristic variables and rice cultivation practices. The results showed that farmers were of productive age, with a low level of formal education but experienced and active in local organizations. The level of application of farmers' ecological agriculture is moderate. The return of straw, tillage, and control of plant pests are the components of cultivation that are least following the principles of ecological agriculture. Internal factors of farmers that correlate with the components of ecological rice cultivation are age, education, length of farming, source of farming knowledge, and land ownership status. Keywords: climate change, paddy field, paddy’s straw return